2014
DOI: 10.1016/j.jocn.2013.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment to trials of late thrombolysis: Lessons from the EXTEND study

Abstract: To increase the percentage of acute stroke patients benefiting from thrombolysis, the utility of expanding the time window of treatment beyond 4.5 hours after stroke onset needs to be investigated. We aimed to identify the target population and the challenges of recruitment of patients for the time window beyond 4.5 hours. Extending the time for Thrombolysis in Emergency Neurological Deficits (EXTEND), a multicentre randomised controlled trial testing the efficacy of thrombolytic therapy in patients with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In a study evaluating the safety and efficacy of IV thrombolysis for patients with wake-up stroke, Hill et al 26 were able to enroll only 20 of 89 screened patients; 19 patients were excluded because well-defined strokes were already present on the initial CT scan. Based on the experience at one EXTEND center, Dagonnier et al 27 found that 70.5% of the 95 patients screened for the trial had wake-up strokes, but only 17 patients had no other exclusion criterion for treatment. Based on these experiences and that of the AbESTT-II, researchers should anticipate that the rates of recruitment in the trials will be slower than expected.…”
mentioning
confidence: 99%
“…In a study evaluating the safety and efficacy of IV thrombolysis for patients with wake-up stroke, Hill et al 26 were able to enroll only 20 of 89 screened patients; 19 patients were excluded because well-defined strokes were already present on the initial CT scan. Based on the experience at one EXTEND center, Dagonnier et al 27 found that 70.5% of the 95 patients screened for the trial had wake-up strokes, but only 17 patients had no other exclusion criterion for treatment. Based on these experiences and that of the AbESTT-II, researchers should anticipate that the rates of recruitment in the trials will be slower than expected.…”
mentioning
confidence: 99%
“…Ongoing trials selecting patients either with WUS (WAKE-UP trial) or beyond the 4.5 time window (EXTEND trial) based on identification of significant salvageable brain tissue may further contribute to better select patients profiting from IVT [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%